An Eco-critical Exegesis of Shona Taboos. Issue 2 (3rd July 2021) - Makaudze, Godwin
Abstract : The emergence in Zimbabwe today of organisations and the promulgation of many pieces of legislation all meant to protect various aspects of the environment do not imply that Zimbabwean societies have never kept a positive eye on their environments. Traditional societies, the Shona in this case, have largely been particular about and enjoyed a sound relationship between the people and their environment. This article is an eco-critical exegesis of Shona taboos, known as zviera, with intent to lay bare the positive attitudes and approaches that traditional societies pay to, and inculcate in members towards various aspects of the environment. It observed that traditional Shona societies use taboos as one of the most powerful environmental awareness and conservation genres, wherein human life is shown as hinged on the animal, vegetative and physical environments which are then supposed to be identified, named, meaningfully and economically exploited and safeguarded from pollution, over-extraction and depletion for the well-being of humanity. These findings have a strong bearing on the positives inherent in Shona traditional ways of achieving environmental awareness even in the contemporary world, and on further research.